Proposed Business Strategy for "Tedja Catering" Maintaining Competitive Advantage - Putri, Santhya Ramadhani; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2014)
Abstract- Tedja catering is the catering services that has been established since 1996. This business started from a hobby and economic pressures, Ms. Ginawati and her husband try hard for his life and the lives of their children. The business issues is Tedja catering have to increase their pprofit and maximize the production capacity everyday Tedja catering customers are office buildings and factories. Growth in factory, office buildings and number of workers has increase every years. This make Tedja catering thought to the increasing customers each year. The method used by observation and interviews to the company. To analyze the internal factors using the business model canvas and value chain analysis, for the external factors using PEST, Porter's five force and competitor analysis then data will be calculated and analyzed by using IFAS and EFAS matrix, and IE matriks. The strategy are market penetration and product development after analyze with IE matrix. To know which of both strategy would be appropriate by using the calculation QSPM. The results of this research are recommending the business strategy with market penetration, the author give an action plan for the next 5 years to make Tedja catering more grow up and better than the other competitor. Keywords: business strategy, catering business, business model canvas